Evolutionary dynamics and functional diversification of BBX transcription factors in C4 grasses from Setaria italica and Setaria viridis - Liu, Jiaxin; Zhang, Haoshan; Zhao, Ling; Wang, Hua; Li, Shen; Wang, Yulu; Li, Lin; Zou, Luming; Zhang, Ting; Cheng, Ruhong; Shi, Zhigang; Zhang, Zhuxin; et al. (Frontiers in Plant Science, 2026)
IntroductionB-box (BBX) transcription factors are key regulators of plant development, growth, and responses to photoperiod. However, their evolutionary dynamics and functional diversification in C4 grass crops are limited.Methods and resultsThe study involved the identification and systematic analysis of 33 BBX genes from Setaria italica (16) and Setaria viridis (17), which were classified into subfamilies I, III, and IV based on phylogenetic relationships. Gene structure and motif analysis revealed conserved patterns within subfamilies, while chromosomal mapping and duplication analysis suggested that dispersed duplication was the primary driver of BBX gene family expansion, with all genes under purifying selection. Comparative genomic analyses across representative species of the Poaceae and Arabidopsis thaliana indicated a contraction of the BBX gene family in C4 grasses. Expression profiling suggests potential functional divergence, with BBX genes exhibiting differential expression patterns associated with development, photoperiod response, and abiotic stress. Cis-acting element analysis further highlighted species-specific regulatory mechanisms. Several SiBBX genes showed clear daily rhythmic expression under long-day photoperiod conditions by quantitative real-time PCR (qRT-PCR). Subcellular localization assays showed that selected SiBBX proteins localize to the nucleus, consistent with their roles as transcription factors.DiscussionOur findings provide insights into the molecular evolution and functional diversification of BBX genes in C4 grasses and offer potential targets for genetic improvement of heading date and stress tolerance in C4 crops.